Global survey of dioxin- and thyroid hormone-like activities in consumer products and toys - Behnisch, Peter; Petrlik, Jindrich; Budin, Clemence; Besselink, Harrie; Felzel, Emiel; Strakova, Jitka; Bell, Lee; Kuepouo, Gilbert; Gharbi, Semia; Bejarano, Fernando; Jensen, Génon K; DiGangi, Joseph; et al. (Environment international, 2023)
BACKGROUND: Children and consumers are exposed to increasingly complex mixtures of known and as-yet-unknown toxic chemicals from toys and products. However traditional chemical analysis methods only evaluate a small number of chemicals at a time thereby restricting consumer awareness of the full range of potentially harmful chemicals in products. METHODS: We used high-throughput effect-based non-animal methods to investigate exposures to complex chemical mixtures of several kinds of brominated flame retardants (BFRs) for their dioxin- and thyroid hormone-like activities in various kinds of consumer products and toys from 26 different countries, on four continents (Africa, America, Asia and Europe) in combination with chemical analysis of various polybrominated flame retardants (BFRs) and their impurities (such as polyhalogenated PCDD/Fs and PBDD/Fs). RESULTS: We found high levels of polybrominated dibenzo-p-dioxins and dibenzofurans (PBDD/Fs) in toys and now, for the first time, also in consumer products that are manufactured from black plastics containing certain brominated flame retardants (BFRs). The presence of PBDD/PBDFs as well as other BFRs in various black plastic materials from additional countries as well as additional kinds of consumer products as confirmed by effect-based in vitro reporter gene DR CALUX and TTR-TRβ CALUX assays as well as congener-specific chemical analysis. We compared total Toxicity Equivalent (TEQ) levels of PBDD/F-TEQs analysed by chemical analysis to by CALUX bioassay measured Biological equivalence (BEQ) concentrations (for further info see at ISO 23196, ISO, 2022). In the case of TBBPA, both chemical and TTR-TRβ CALUX analysis measure direct the amount of TBBPA. Finally, the daily ingestion of 2,3,7,8-TCDD equivalents from PBDD/Fs-contaminated plastic toys by child mouthing habits have been related to our earlier study (Budin et al., 2020). CONCLUSIONS: Interaction of children with such contaminated plastics may significantly contribute to the daily uptake of dioxin- and thyroid hormone transport disrupting-like compounds. Effect-based bioassays for dioxin- and thyroid hormone-like activities are relevant to pick-out such complex mixtures of known and yet unknown (and therefore not regulated) substances for safer and more sustainable plastics. Low POPs Content Levels and other mechanisms set under the Basel and Stockholm Conventions are set far too high to prevent a significant flow of BFRs and PBDD/Fs into consumer products.
Keywords: Tetrabromo-bisphenol A (TBBPA); dioxiny; polychlorované dibenzodioxiny; Humans; retardanty hoření; Polychlorinated Dibenzodioxins; dítě; Plastics; plastické hmoty; Child; Dioxins; Flame Retardants; lidé; DR CALUX; TTR -TRβ CALUX; dibenzofurany; Dibenzofurans; komplexní směsi; Consumer products; hormony štítné žlázy; Complex Mixtures; Polybrominated dibenzo-p-dioxin and dibenzofurans (PBDD/PBDFs); Thyroid Hormones